Implementation Of Plant Cultivation Through Social Forestry In An Effort To Reduce The Climate Crisis In Dusun Jepang Of Bojonegoro - Arianti, Marshiela Putri; Alawi*, Muammar (Riwayat: Educational Journal of History and Humanities, 2024)
This research was conducted in the Dusun Jepang of Margomulyo Village, Bojonegoro Regency through village development activities from the National Development University "Veteran" East Java. The research carried out by the author is a form of development for the residents of Dusun Jepang and at the same time preserving the natural environment in the village. The aim of this research is to reduce the climate crisis in Dusun Jepang so that residents living in the village can plant plants without worrying about the plants dying due to temperatures that are too hot. This research was carried out through interviews and field observations. In addition, the author documents the results of observations as data. The village has few residents and large areas of land. The author plants plants and carries out outreach about Social Forestry in an effort to improve the welfare of the residents and environment in the village.